Pragmatic Deixis in King Charles III’s Inauguration Speech - Ayu Ratri; Barli Bram (Journal of Pragmatics Research, 2023)
Deixis in English is a phenomenon of understanding words and phrases by considering contexts and actual speech action. Second learners can employ the pragmatic deixis in various literary works or other media dimensions to comprehend the Meaning of words and utterances. Hence, this study attempted to know the types of deixis in King Charles III Inaugural speech. The researchers obtained the transcript from the New York Times and analysed it using descriptive research to explore and explain the deixis types in the speech in more detail. The writers used Cruse’s (2000) theory to indicate the five types of deixis. The data revealed that all types of deixis occurred in speech, including person deixis, spatial deixis, temporal deixis, discourse deixis, and social deixis. The type of deixis that appears most often is person deixis, with a percentage of 71%. Meanwhile, the deixis that appears the least is social deixis, with a percentage of only 3%. The spatial and discourse deixis each have a percentage of 9%, followed by temporal deixis with a percentage of 8%. The result of this study is likely to enrich second learners of English's knowledge and vocabulary of pragmatic studies, primarily the phenomenon of deixis.